Penyalahgunaan Benda Virtual dalam Permainan Game Online di Indonesia - Putu Bagus Gandiwa Dhanandjaya; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Konstruksi Hukum, 2022)
Technological developments present a variety of entertainment such as offline and online games. Online games are in great demand among children and teenagers. The purpose of playing online games in Indonesia is to find out the positive impact of online games for students, to find out the negative impacts of online games for students, and to find out how to overcome the negative effects of online games buying and selling items that belong to virtual objects. Although it doesn't have a real form, these virtual objects are considered valuable for players. The normative legal research method will certainly generate new arguments. Due to the online buying and selling of virtual objects, of course there will be misuse of these virtual objects to commit fraud. How is the arrangement of virtual objects in online games in Indonesia. How are criminal sanctions against abuse of virtual objects in online games in Indonesia. In writing this research, normative legal research is used, namely legal research carried out by examining library materials or secondary data, namely by studying and reviewing legal principles and positive legal principles derived from library materials and legislation. The conclusion from this research is that virtual objects can be called objects according to the law of objects in Indonesia and there are criminal sanctions against perpetrators of abuse of virtual objects.